Os acervos documentais referentes aos Salões de Arte de Pelotas (1977-1981): história e memória - Oliveira, Aydê Andrade de (2011)
This work results from a historical research developed from the mapping and location of the recording means in its many forms. Thus, the object of this research are both the public and private documental collections about the Art Salons in Pelotas (1977-1981). The main goal was to systematise these collections as means of ensuring the preservation, retrieval and dissemination of the informational content. Promoted by the Education Office, these salons were conceived and organised by the Cultural Affairs Coordinator, Nelson Abbott de Freitas, who recorded those exhibitions with photos, newspaper clippings and other documents, playing also the role of guardian of the memory, building albums of the events´ history. These salons called attention for their repercussion among the press media, which provided a great amount of articles published in local, regional and national newspapers. The artistic and cultural expressions that derived from these salons were considered as cultural objects which symbolize the local identity and the social memory of culture in Pelotas, represented by the awarded works at the salons, which were exhibited at the Nelson Abbott de Freitas Gallery. The choice of this profile is due to the documentation composed by the audiovisual collection Art in Pelotas - The Art Salons, produced by the South Center for Integrated Teleducation of the Federal University of Pelotas, located at the university´s Social Sciences Library. The work emphasises the importance of records and, from the documental analysis of these collections´ contents, shows the importance of systematic reconstruction of the history and the memory of the Art Salons in Pelotas.